(untitled) (Siddhanta’s International Journal of Advanced Research in Arts & Humanities, 2025)
We all speak about gender equality, but the Indian constitution, unfortunately, is far from realistic. True, there was a period when the government had to include specific provisions into the constitution for women in order to assure equality, but some of these laws are blatantly discriminatory towards males. We want to be able to speak about a world in 2030 that has achieved gender equality, a globe that is 50:50. In India, men’s rights campaigners recently won a big win when the Supreme Court declared them to be the victims of domestic abuse. However, the courts did not make the statute gender-neutral. "They said that Indian women were making false domestic violence charges.’’ The moment has come for males to no longer be seen as the recurring issue, but rather as part of the solution. Some laws in India are not only gender biased, but they also need to be amended as quickly as possible. Purush Ayog, or the National Men’s Commission, is a statutory organization that may make these changes. This paper examines the Men’s Rights in India, which are hampered by our Constitution’s gender bias, as well as the reasons for the lack of men-centric legislation.